Testing the mutagenic potency of chemical substances in a linear host-mediated assay I. Experimental microbiological basis - Grafe, Alfred; Lorenz, Rolf; Vollmar, Joachim (Mutation Research/Environmental Mutagenesis and Related Subjects, 1975)
By the use of the mutagenic substance hydrazine sulphate it is shown that the currently used single determination method for determining point mutations in host-mediated assays with calculation of mutation frequencies can lead to erroneous results. The microbiological basis for a linear method is presented in which the population growth of the auxotrophic and substance-induced mutants used in the test can be described mathematically during their logarithmic growth phase with regression lines.